Genome-Wide Identification of Dicer-Like, Argonaute, and RNA-Dependent RNA Polymerase Gene Families in Brassica Species and Functional Analyses of Their Arabidopsis Homologs in Resistance to Sclerotinia sclerotiorum - Cao, Jia-Yi; Xu, You-Ping; Li, Wen; Li, Shuang-Sheng; Rahman, Hafizur; Cai, Xin-Zhong (Frontiers in Plant Science, 2016)
RNA silencing is an important mechanism to regulate gene expression and antiviral defense in plants. Nevertheless, RNA silencing machinery in the important oil crop Brassica napus and function in resistance to the devastating fungal pathogen Sclerotinia sclerotiorum are not well understood. In this study, gene families of RNA silencing machinery in B. napus were identified and their role in resistance to S. sclerotiorum was revealed. Genome of the allopolyploid species B. napus possessed 8 Dicer-like (DCL), 27 Argonaute (AGO) and 16 RNA-dependent RNA polymerase (RDR) genes, which included almost all copies from its progenitor species B. rapa and B. oleracea and three extra copies of RDR5 genes, indicating that the RDR5 group in B. napus appears to have undergone further expansion through duplication during evolution. Moreover, compared with Arabidopsis, some AGO and RDR genes such as AGO1, AGO4, AGO9 and RDR5 had significantly expanded in these Brassica species. Twenty-one out of 51 DCL, AGO and RDR genes were predicted to contain calmodulin-binding transcription activators (CAMTA)-binding site (CGCG box). S. sclerotiorum inoculation strongly induced the expression of BnCAMTA3 genes while significantly suppressed that of some CGCG-containing RNA silencing component genes, suggesting that RNA silencing machinery might be targeted by CAMTA3. Furthermore, Arabidopsis mutant analyses demonstrated that dcl4-2, ago9-1, rdr1-1, rdr6-11 and rdr6-15 mutants were more susceptible to S. sclerotiorum, while dcl1-9 was more resistant. Our results reveal the importance of RNA silencing in plant resistance to S. sclerotiorum and imply a new mechanism of CAMTA function as well as RNA silencing regulation.